2004
DOI: 10.1080/13576500342000239
|View full text |Cite
|
Sign up to set email alerts
|

Left‐ and right‐handed children's drawing performance: Is there any difference?

Abstract: The aim of the present study was to investigate the effect of hand preference on children's drawing development. An equal number of left- and right-handed children (N = 182), aged 7 to 12 years were asked to complete four different drawing tasks. During the drawing process, directionality of horizontal, vertical, and circular strokes as well as sequencing was recorded. Each drawing was scored according to the developmental stage to which is corresponded. It was found that drawing performance improved with age,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 23 publications
1
7
0
2
Order By: Relevance
“…(2003) also found that laterality is only weakly associated with children's cognitive ability. Vlachos and Bonoti (2004) found no significant differences in performance across four drawing‐related tasks by handedness, although the study used only a sample of 182 children aged between 7 and 12 years.…”
Section: Causes Of Handedness and Their Consequences For Health Anmentioning
confidence: 82%
“…(2003) also found that laterality is only weakly associated with children's cognitive ability. Vlachos and Bonoti (2004) found no significant differences in performance across four drawing‐related tasks by handedness, although the study used only a sample of 182 children aged between 7 and 12 years.…”
Section: Causes Of Handedness and Their Consequences For Health Anmentioning
confidence: 82%
“…The EHI is a well-known instrument used to determine hand preference for specific tasks within a variety of research conditions (Bishop et al, 1996). The Citation Index indicates that it has been the most widely used inventory in the literature (Vlachos & Bonoti, 2004). The EHI has been standardized on several populations (McMeekan & Lishman, 1975;Williams, 1986) and administered to children (Bishop, 2006;Brito, Lins, Paumgartten, & Brito, 1992;Dane & Gümüstekin, 2002;Ostatníková, Laznibatová, Putz, Maťašeje, Dohnányiová, & Pastor, 2000;Ross, Lipper, & Auld, 1992).…”
Section: Measure Of Handednessmentioning
confidence: 99%
“…Some did not find differences regarding the measured performances, e.g., nonverbal intelligence, reading, and spelling (Mayringer & Wimmer, 2002), reading skills and intelligence (McManus, Sik, Cole, Mellon, Wong, & Kloss, 1988), drawing skills (Vlachos & Bonoti, 2004b), and writing performance (Vlachos & Bonofi, 2004a). Others pointed to differences between left-and right-handed children (depending on their hand preference across different tasks), i.e,, overrepresentation of left-handed children in the group of poor writers (Vlachos & Bonoti, 2004a) and poorer drawing performance of left-handed children (Karapetsas & Vlachos, 1997), Tan (1985) found that children lacking clear hand preference showed worse gross and fine motor performance, Karapetsas and Vlachos (1997) postulated difterences in brain development, in particular regarding the myelinisation of the corpus callosum and the lateralization of the brain, as possible reasons why children with right hand preference and girls showed better performances in certain periods of development, Crow, Crow, Done, and Leask (1998) assessed relative hand skill and referred to the point of equal hand skill as a point of "hemispheric indecision" (p. 1277).…”
mentioning
confidence: 97%